Infectivity inhibition by overlapping synthetic peptides derived from the gH/gL heterodimer of herpes simplex virus type 1. (14th February 2017) - Franci, Gianluigi; Falanga, Annarita; Zannella, Carla; Folliero, Veronica; Martora, Francesca; Galdiero, Marilena; Galdiero, Stefania; Morelli, Giancarlo; Galdiero, Massimiliano
Abstract : Herpes simplex virus (HSV) is a human pathogen that infects epithelial cells. The cutaneous lesions, caused by the virus, spread to the nervous system creating several complications. Fusion of host membranes with the viral envelope is mandatory and mediated by a group of glycoproteins conserved in all Herpesviridae subfamilies, such as the glycoproteins B (gB), H (gH), L (gL) and D (gD). We investigated the inhibitory activity mediated by synthetic overlapping peptides spanning the entire ectodomains of gH and gL glycoproteins. We have performed a brute analysis of the complete gH/gL heterodimer in order to explore the inhibitory activity of peptides modelled on these glycoproteins against HSV‐1 infection. Twenty‐four of the gH peptides at a concentration of 150 μM reached the 50% of inhibition cut‐off. Interestingly, they are mainly located in the gH carboxy‐terminal domain. None of the gL peptides had a clear inhibiting effect. No peptide toxicity was observed by lactate dehydrogenase assay at the concentrations used in our experimental conditions. HSV‐1 therapy is based on acyclovir treatment, but some resistant strains are emerging. In this scenario, innovative approaches for HSV‐1 treatment are necessary. Our data support the direct involvement of the described domains in the process of virus penetration; therefore, these results are of relevance to the potential development of novel therapeutic compounds to prevent HSV‐1 infections. Copyright © 2017 European Peptide Society and John Wiley & Sons, Ltd. Abstract : In vitro screening of overlapping synthetic peptides derived from HSV‐1 glycoproteins for virus inhibition.